1998
DOI: 10.1161/01.str.29.2.433
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Stenosis From Intracranial Atherosclerosis by Serial Angiography

Abstract: Background and Purpose-Knowledge of the natural history of stenoses due to intracranial atherosclerosis may be useful for evaluating possible treatments such as angioplasty. Methods-We retrospectively reviewed records over a 7-year period to identify patients with intracranial atherosclerotic stenoses and serial angiograms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
1
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 35 publications
0
78
1
4
Order By: Relevance
“…Similar data were obtained in other angiography studies, which showed high-grade intracranial lesions in 35%-49% of cases. 1,7,13 In our study, we did investigate 2 ICA segments in detail, especially those in which the MR imaging artifact problem frequently occurs and in which angioplasty may not be complicated by an extremely tortuous arterial course. 19 Tandem stenosis of the ICA is of special interest in patients undergoing surgical ICA revascularization or stent placement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar data were obtained in other angiography studies, which showed high-grade intracranial lesions in 35%-49% of cases. 1,7,13 In our study, we did investigate 2 ICA segments in detail, especially those in which the MR imaging artifact problem frequently occurs and in which angioplasty may not be complicated by an extremely tortuous arterial course. 19 Tandem stenosis of the ICA is of special interest in patients undergoing surgical ICA revascularization or stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Ischemic stroke due to atherosclerosis of intracranial large arteries has been reported in approximately 8%-29% of adults in general, with a higher prevalence in African and Asian populations. [4][5][6] The intracranial internal carotid artery (ICA) is the most common location for intracranial stenosis of Ͼ50%; such cases compose up to 49% of all intracranial artery stenoses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C erebral arterial stenoses can be caused by a wide range of diseases such as central nervous system infectious or inflammatory vasculitis, 1-3 intracranial atherosclerosis, 4 or vasospasm. 5,6 The diagnosis of intracerebral arterial stenosis can be clinically challenging because the initial presentation is highly variable, with focal to diffuse neurological manifestations and acute to chronic evolution.…”
mentioning
confidence: 99%
“…26 Because the progression of MCA stenosis appears to be quite common, suggested by 61% serial angiography progression of stenosis during approximately 2 years, routine monitoring of stenosis with time may be even more important than in carotid disease. 27 Knowing the prognosis of particular types and degrees of stenotic MCA disease is important in determining target populations for angioplasty, stent placement, or medical management.…”
Section: Risk Management and Outcomesmentioning
confidence: 99%